Бронзова фігурка від процесійного хреста лімозької роботи XIII ст. із Нижнього Подніпров’я - Єльніков, М.В. (Археологія, 2005)
Статтю присвячено публікації знахідки бронзової фігурки святого від прецесійного хреста «торгового типу» західноєвропейських ювелірів із пам’ятки Мамай-Сурка біля с. Велика Знам’янка Кам’янсько-Дніпровського р-ну Запорізької обл. В статье публикуется находка бронзовой фигурки святого от процессионного креста «торгового типа» лиможских мастеров, обнаруженная на поселении Мамай-Сурка в Нижнем Поднепровье. По манере исполнения изделие датируется второй половиной XIII в. и, наряду с христианскими персонажами из Надпорожья представляет собой важный исторический источник изучения торговых связей региона со странами Западной Европы в золотоордынский период, которые осуществлялись при посредничестве Киева. The article lays open to the public a bronze figure of a saint from a processional «trade-type» cross made by a craftsman from Limoges, discovered at the Mamaj-Surok settlement in the Lower-Dnipro Region. The manner of execution is dated back to the second half of the 13th century. Besides Christian personages from Nadporizhzia this artifact represents an important historical source for the study of the trade connections of the region with the countries of the Western Europe in the Golden Horde period, which were carried out with the mediation of Kyiv.